Ambiguity and Excuse-Driven Behavior in Charitable Giving - Thomas Garcia; Sebastien Massoni; Marie Claire Villeval (Institute of Labor Economics (IZA), 2019)
A donation may have ambiguous costs or ambiguous benefits. Behavior in a laboratory experiment suggests that individuals use this ambiguity strategically as a moral wiggle room to act less generously without feeling guilty. Such excuse-driven behavior is more pronounced when the costs of a donation â exteuro“ rather than its benefits â exteuro“ are ambiguous. However, the importance of excuse-driven behavior is comparable under ambiguity and under risk. Individuals exploit any type of uncertainty as an excuse not to give, regardless of the nature of this uncertainty.
Keywords: C91; D64; D81; 330; social preferences; charitable giving; excuse-driven behavior; ambiguity; experiment